An investigation into fraud and corruption risk management policies and procedures at institutions of higher learning - Makhooane, Stephen Malefane (Rhodes University, Faculty of Commerce, Rhodes Business School, 2012)
Fraud and corruption cost South Africa billions of rand yearly. Institutions of higher learning are no less vulnerable to fraud and corruption than other organisations, but are also subject to risks that are unique to academia. The Public Finance Management Act. No.1 of 1999 requires Public entities including the councils (university or college controlling body) of public institutions of higher learning to adopt enterprise risk management, which includes a fraud and corruption risk management policy and procedures. The function of the fraud and corruption policy is to provide an objective strategy to prevent, detect and investigate any possible irregularity in order to prevent further loss in line with Corporate Governance requirements. The anti-fraud and corruption strategy measures include setting the appropriate tone by management of the institution, being proactive (fraud risk assessments), and being reactive (reporting process, investigation and taking appropriate action). The actions include disciplinary action and criminal or civil proceedings in order to recover assets lost. The procedures address the implementation of the policy. This research focused on identifying the relevant issues that could be included in the formulation of fraud and corruption risk management policies and procedures for institutions of higher learning. The research was conducted using a qualitative methodology consisting of a document analysis and interviews. It was found that, out of eleven institutions of higher learning investigated only one institution meets the criteria set out in the framework developed in the research as an assessment tool. The other institutions involved in the research did not have fraud and corruption risk management policies or procedures and therefore did not comply with the Public Finance Management Act.
Keywords: Fraud -- South Africa -- Prevention; Corruption -- South Africa -- Prevention; Risk management -- South Africa -- Evaluation; Education, Higher -- South Africa -- Finance